Thermophysical and spectroscopic studies of magnesium salicylate–trisodium citrate/chloride mixtures - Mashahid Hussain Choudhary; Nabaparna Chakraborty; Kailash Chandra Juglan (Chemical Thermodynamics and Thermal Analysis)
The examination of volumetric and acoustic behaviour in magnesium salicylate with sodium chloride (NaCl) and trisodium citrate (C6H5Na3O7) provide valuable insights into molecular interactions. To investigate these interactions, solution densities and speed of sound were determined for two and three component systems (magnesium salicylate + water + NaCl/C6H5Na3O7) at four different temperatures (T = 288.15–318.15 K) and at varying concentrations. Data obtained from experiments were processed to compute key parameters such as apparent and partial molar volumes, apparent and partial molar isentropic compressibilities, molar expansibilities, and isobaric thermal expansion coefficients. Additionally, temperature-dependent derivative properties (∂Eϕ0/∂T)pprovided deeper insight into solute-solvent behaviour and the structure-creating or disrupting tendencies of NaCl and C₆H₅Na₃O₇. These parameters were evaluated to understand molecular interactions, hydrogen bonding, and structural changes occurring in the system. To gain further molecular-level insight, FTIR spectroscopy was performed for the binary and ternary systems. The results demonstrated strong solute–solvent interactions, structure-creating behaviour, and reduced compressibility in ternary systems. FTIR spectroscopy confirmed these findings by showing O–H stretching band shifts up to 3302 cm⁻¹, indicating the presence of intermolecular hydrogen bonding. The combined results from volumetric and acoustic, analyses were interpreted using co-sphere overlap shell model and McMillan-Mayer theory, providing a detailed analysis of solvation dynamics and intermolecular interactions in the studied systems. By encouraging improvements in pharmaceutical procedures and sustainable practices, the study's conclusions not only enrich our knowledge of molecular interactions but also help us achieve important Sustainable Development Goals (SDGs).